Developing institutions for cancer care in low-income and middle-income countries: from cancer units to comprehensive cancer centres. Issue 8 (August 2018) - Sirohi, Bhawna; Chalkidou, Kalipso; Pramesh, C S; Anderson, Benjamin O; Loeher, Patrick; El Dewachi, Omar; Shamieh, Omar; Shrikhande, Shailesh V; Venkataramanan, R; Parham, Groesbeck; Mwanahamuntu, Mulindi; Eden, Tim; et al.
Summary: Global cancer centres operate across different sizes, scales, and ecosystems. Understanding the essential aspects of the creation, organisation, accreditation, and activities within these settings is crucial for developing an affordable, equitable, and quality cancer care, research, and education system. Robust guidelines are scarce for cancer units, cancer centres, and comprehensive cancer centres in low-income and middle-income countries. However, some robust examples of the delivery of complex cancer care in centres in emerging economies are available. Although it is impossible to create an optimal system to fit the unique needs of all countries for the delivery of cancer care, we summarise what has been published about the development and management of cancer centres in low-income and middle-income countries so far and highlight the need for clinical and political leadership.